Highmolecular glutenin subunits on the M4 mutant lines of spring wheat - donors of productivity and high protein content grain (Experimental biology, 2015)
Сomposition of the storage proteins of glutenin on productive and high-protein content in grain on samples of M4 mutant lines of spring wheat (Triticum aestivum L.) from the created mutant collection on the genetic basis of grades and Jenis by exposure to different doses of gamma radiation is determined
Keywords: M4 the productive mutant forms of wheat donor; glutenins; high protein grain content